2004
DOI: 10.1128/jvi.78.12.6409-6419.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Binding of Hepatitis C Virus Core to gC1qR on CD4+and CD8+T Cells Leads to Impaired Activation of Lck and Akt

Abstract: Hepatitis C virus (HCV) is a serious and growing threat to human health, having infected more than 170 million people worldwide. A remarkable feature of HCV is its ability to establish chronic infection. Indeed, the virus persists in Ͼ85% of patients following acute infection. These individuals carry an increased risk of developing various liver diseases, including cirrhosis and hepatocellular carcinoma (9). Unfortunately, no vaccine or effective treatment for HCV is currently available, and the mechanism(s) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
99
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 46 publications
4
99
1
Order By: Relevance
“…A correlation between reduced IL-2 production of CD4 + T cells (84) and dysfunction of CD8 + T cells has been observed, and reduced IL-2-activated killing by CD3 + CD56 + T cells has recently been shown to precede the development of chronic hepatitis C (85). HCV core has been implicated in this process via binding to the receptor for the globular head domains of complement component C1q (gC1qR) and inhibition of Lck/Akt activation and T cell function (86). Dysfunctional HCV-specific T cells express the inhibitory receptor PD-1 (87,88), which is a direct result of chronic antigenic stimulation and decreases when HCV mutates in T cell epitopes (89).…”
Section: Chronic Hcv Infection: Exhaustion Of Hcv-specific T Cellsmentioning
confidence: 99%
“…A correlation between reduced IL-2 production of CD4 + T cells (84) and dysfunction of CD8 + T cells has been observed, and reduced IL-2-activated killing by CD3 + CD56 + T cells has recently been shown to precede the development of chronic hepatitis C (85). HCV core has been implicated in this process via binding to the receptor for the globular head domains of complement component C1q (gC1qR) and inhibition of Lck/Akt activation and T cell function (86). Dysfunctional HCV-specific T cells express the inhibitory receptor PD-1 (87,88), which is a direct result of chronic antigenic stimulation and decreases when HCV mutates in T cell epitopes (89).…”
Section: Chronic Hcv Infection: Exhaustion Of Hcv-specific T Cellsmentioning
confidence: 99%
“…Recombinant C protein also has a number of inhibitory effects on TcR signaling, including impaired activation of the signaling molecules Lck, ZAP-70, Akt, ERK, and MEK, upregulation of T-cell expression of the negative regulator PD-1, and cell cycle arrest. These effects have been reported to be dependent upon the interaction of C protein with the complement receptor gC1qR (72,(166)(167)(168)(169), which may facilitate the entry of C protein into T cells (31). In support of the importance of C protein in vivo, transgenic mice with C protein expression targeted to T cells by the CD2 promoter showed markedly depressed IL-2 and gamma interferon production after anti-CD3 stimulation of splenocytes (141).…”
Section: (And Other Morbilliviruses)mentioning
confidence: 99%
“…We have previously demonstrated that HCV core can inhibit T-cell proliferation through interaction with gC1qR on T lymphocytes (17,(36)(37)(38). This finding, in light of the observation that free core particles circulate in the bloodstreams of HCV-infected patients (24,25), is particularly noteworthy in HCV pathogenesis since the binding of C1q, the natural ligand for gC1qR, to T lymphocytes leads to immunosuppression (8,11).…”
mentioning
confidence: 99%
“…Despite HCV core being well conserved among various genotypes, the core protein from genotype 1a is able to dampen the host immune response (37), but the expression of core protein from genotype 1b in transgenic mice did not elicit such an effect (22). Thus, studies of the immunomodulatory functions of different HCV core clinical isolates will be valuable for understanding whether there is an intrinsic link between the sequence of core and the dysregulation of T-cell function in resolved and chronic HCV infections.…”
mentioning
confidence: 99%